Introduction and adoption of innovative invasive procedures and devices in the NHS: an in-depth analysis of written policies and qualitative interviews (the INTRODUCE study protocol). Issue 8 (26th August 2019) - Cousins, Sian; Richards, Hollie; Zahra, Jesmond; Elliott, Daisy; Avery, Kerry; Robertson, Harry F; Paramasivan, Sangeetha; Wilson, Nicholas; Mathews, Johnny; Tolkien, Zoe; Main, Barry G; Blencowe, Natalie S; et al.
Abstract : Introduction: Innovation is key to improving outcomes in healthcare. Innovative pharmaceutical products undergo rigorous phased research evaluation before they are introduced into practice. The introduction of innovative invasive procedures and devices is much less rigorous and phased research, including randomised controlled trials, is not always undertaken. While the innovator (usually a surgeon) may introduce a new or modified procedure/device within the context of formal research, they may also be introduced by applying for local National Health Service (NHS) organisation approval alone. Written policies for the introduction of new procedures and/or devices often form part of this local clinical governance infrastructure; however, little is known about their content or use in practice. This study aims to systematically investigate how new invasive procedures and devices are introduced in NHS England and Wales. Methods and analysis: An in-depth analysis of written policies will be undertaken. This will be supplemented with interviews with key stakeholders. All acute NHS trusts in England and Health Boards in Wales will be systematically approached and asked to provide written policies for the introduction of new invasive procedures and devices. Information on the following will be captured: (1) policy scope, including when new procedures should be introduced within a formal research framework; (2) requirements for patient information provision; (3) outcome reporting and/or monitoring. Data will be extracted using a standardised form developed iteratively within the study team. Semistructured interviews with medical directors, audit and governance leads, and surgeons will explore views regarding the introduction of new invasive procedures into practice, including knowledge of and implementation of current policies. Ethics and dissemination: In-depth analysis of written policies does not require ethics approval. The University of Bristol Ethics Committee (56522) approved the interview component of the study. Findings from this work will be presented at appropriate conferences and will be published in peer-reviewed journals.